Representasi Emosi Dalam Komunikasi Interpersonal melalui Musik Video Dunia Tipu-Tipu - Syahida, Santia Indah; Mardiana, Lisa (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Emotional expression is a form of nonverbal communication that can strengthen meaning in interpersonal relationships. This study aims to examine the representation of emotional expressions in interpersonal communication in the music video